Memory in the stone : rock art landscape at Cerro Colorado as a negotiation space for social memory - Recalde, María Andrea (2018)
Fil: Recalde, María Andrea. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Escuela de Historia; Argentina.